Hot-pressing design of tubular polyester nonwoven lining material for pipeline rehabilitation. Issue 3 (June 2022) - Fu, Lisong; Zhang, Shujie; Wang, Rui; Cao, Guoquan; Jing, Mengke; Zhang, Yating; Zhang, Ziwei
In view of the strength loss and dimension shrinkage of polyester nonwoven used for the sewage pipeline in the hot-pressing process, the response surface methodology was proposed to optimize the technological parameters of lining material. Select the temperature, time and pressure to enhance the hot-pressing process of lining material with the response value of the rate of dimensional change and tensile strength. The results showed that the temperature was 180°C, time was 3s, and pressure was 2.8MPa. Under this process, the rate of dimensional change was 4.23%, transverse tensile strength was 7.95MPa, and longitudinal tensile strength was 5.26MPa. It showed that the response surface methodology had practical application value, and provided a theoretical basis for the hot-pressing parameters of lining material with maximum tensile strength and minimum dimensional shrinkage. The paper also tested the adhesive strength, air permeability and water permeability of lining material under the optimal process, founding that the prepared material had excellent adhesive strength, air permeability, water permeability, and could meet the construction requirements of pipeline rehabilitation and the use requirements of conveying medium.